Prinsip Syariah Sebagai Alternatif Dalam Transaksi Perbankan - Afifatunnisa, (2021)
Islamic banking in Indonesia is currently experiencing quite good development from year to year. Muslims as the largest population in Indonesia are an opportunity for Islamic banks. Therefore, the Chairman of the Islamic Economic Community, Erick Thohir, hopes that each Islamic bank can maximize its performance so that the Indonesian people can contribute and take advantage of existing Islamic finance. Sharia principles in banking transactions are a good system seen from the current performance of Islamic banks which continue to develop so that they can compete with conventional banks. In addition, as Muslims, choosing a islamic bank in daily life is a form of business from staying away from usury which is prohibited by Allah SWT. Bank Pembiayaan Rakyat Syariah (BPRS or Rural Bank), which target the lower middle class as customers, in addition to helping the community with the various products offered, the application of sharia principles is of course also very helpful because of the agreed profit sharing system or fee for cooperation between the two parties. This research aims to understand the application of sharia principles in BPRS with BPRS Harta Insan Karimah Cibitung as the object of research so that sharia principles which are the concepts of Islamic banking can be used as an alternative in banking transactions. Then with the better performance, BPRS banks can compete with conventional banks.